Antonio Gramsci and the May 1919 Chronicles of L’Ordine Nuovo (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2024)
This work presents the translation of the first four chronicles by Antonio Gramsci published in L’Ordine Nuovo newspaper, all in May 1919, unpublished in Portuguese Language. The aim is to explore the historical and political relevance of these texts and highlight the current relevance of the author’s ideas. Each chronicle was historically contextualized and analyzed to make evident Gramsci’s vision of socialism, the working class and the need for social transformation. Among the main findings, Gramsci’s strong criticism of the bourgeoisie and the capitalist system stands out, as he considered them incapable of promoting post-war reconstruction. The author presents the proletariat as the true agent of change, which must be guided by a socialist faith and critical education. Another important finding is the defense of an authentic socialism, free from concessions and superficial pragmatisms, and of an absolute break with the repressive structures of capitalism. Finally, L’Ordine Nuovo is characterized as an instrument of revolutionary education, essential to prepare the working class for the future socialist state. It is still possible to perceive the permanence of Gramsci’s work in contextualization with the current period.Keywords: Chronicles of L’Ordine Nuovo. Antonio Gramsci. Political writings. Revolutionary education. Social transformation.